PECULIARITIES OF NATIONAL LEGISLATION IN THE FIELD OF URBAN PLANNING: Array - Vishnevsky, D. (Municipal economy of cities. Series: «Economy science», 2021)
In modern conditions of territorial development, rational processes of urbanization are especially important. Lessons of economic activity have shown that the solution of important problems of innovative economic and social development of territories is impossible without the organization of fundamentally new relations in the urban planning system, improvement of methods of territorial management, change of management style, psychology and thinking of territorial development, expansion and deepening democracy, increasing the responsibility of all parts of the management of territories. The basis for regulating the processes of general planning at the national and territorial levels is the regulatory and legal support of the urban planning system. According to the world experience, the main requirements for the regulatory support of general planning processes are the following: informativeness and availability of data for all categories of stakeholders in urban planning; development of the system of public control, monitoring of general planning processes, which provides increase of transparency of town-planning processes; ensuring the preservation of cultural, archaeological, architectural, historical heritage in the urban planning system; reduction of corruption in the urban planning system; ensuring the processes of deregulation of the urban planning system as a leading world experience in the organization of regulatory processes. The formation of settlement systems is a multifactorial process, so the modeling of such systems requires a detailed analysis of the functions they perform and their weight priorities for the population. These tasks should be implemented by introducing innovative solutions into the system of legislative support, which is the task of this article. Therefore, it is advisable to determine the prospects for the development of spatial planning systems in Ukraine in accordance with leading global trends and factors of external and internal influence.